2019
DOI: 10.1007/s11229-018-02062-z
|View full text |Cite
|
Sign up to set email alerts
|

Lying, fast and slow

Abstract: Researchers have debated whether there is a relationship between a statement's truthvalue and whether it counts as a lie. One view is that a statement being objectively false is essential to whether it counts as a lie; the opposing view is that a statement's objective truth-value is inessential to whether it counts as a lie. We report five behavioral experiments that use a novel range of behavioral measures to address this issue. In each case, we found evidence of a relationship. A statement's truth-value affe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…In some of their experiments, participants explicitly and unprompted distinguished between trying to lie and actually lying, or based their lie attribution on perspective‐taking, which suggests that such responses are not unnatural. Against this background, Turri and Turri (2021) conclude that experimental evidence suggests a conceptual link between lying and truth‐value, and that at present, the best supported interpretation of the link is that, as in Coleman and Kay (1981) and Hardin (2010), (i) our ordinary lying concept is a prototype concept, summarising falsity as one of its central tendencies. On this view, falsity is essential to the ordinary concept, because the prototypical lie is false, but being false is not strictly necessary for a lie.…”
Section: Wavering Intuitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of their experiments, participants explicitly and unprompted distinguished between trying to lie and actually lying, or based their lie attribution on perspective‐taking, which suggests that such responses are not unnatural. Against this background, Turri and Turri (2021) conclude that experimental evidence suggests a conceptual link between lying and truth‐value, and that at present, the best supported interpretation of the link is that, as in Coleman and Kay (1981) and Hardin (2010), (i) our ordinary lying concept is a prototype concept, summarising falsity as one of its central tendencies. On this view, falsity is essential to the ordinary concept, because the prototypical lie is false, but being false is not strictly necessary for a lie.…”
Section: Wavering Intuitionsmentioning
confidence: 99%
“…On this view, falsity is essential to the ordinary concept, because the prototypical lie is false, but being false is not strictly necessary for a lie. Everybody agrees that if true lies exist, they are rare and atypical occurrences; indeed, Turri and Turri (2021) found evidence that true lies are not prototypical. However, (FALSITY) requires that, as a matter of necessity, lies are false, and so far, given the methodological problems identified by Wiegmann et al (2016) with Turri and Turri's study, no clear‐cut experimental evidence in its support has emerged so far.…”
Section: Wavering Intuitionsmentioning
confidence: 99%
“…Marsili 2016, 299, Wiegmann, Rutschmann, and Willemsen 2017, §3, Wiegmann and Meibauer 2019. In light of these criticisms and further empirical research, Turri and Turri (2019) retreated to the weaker (and much less controversial, cf. Coleman and Kay 1981) claim that only prototypical lying requires falsity.…”
Section: Blameworthiness and Internal Requirements For Knowledgementioning
confidence: 99%
“…Recently, the subjective view on lying was challenged by Turri and Turri (, see also ). They presented participants with the following scenario:
Jacob's friend Mary recently posted information on the internet that will alert the public to serious government corruption.
…”
Section: Empirical Studies On the Concept Of Lyingmentioning
confidence: 99%
“…Recently, Turri and Turri () also argued that lying is a prototype concept that includes falsity. Their experiments showed that objective falsity facilitates lie judgments, e.g., making it more likely that a case is considered as lying and reducing the time to make such a judgment.…”
mentioning
confidence: 99%